Step 1: Set up the equations
Let's denote the two numbers as x and y. From the problem, we know that:
- The sum of the two numbers is 37; thus, we have the equation x + y = 37
- The difference of the two numbers is 11; therefore, we have the equation x - y = 11
Step 2: Solving the equations
Now, we can proceed to solve these equations system.
If you add these two equations:
(x + y) + (x - y) = 37 + 11, you get:
2x = 48.
After you find that equation, it's obvious that you can find x by dividing both sides of it by 2 to solve for 'x', to get:
x = 48 / 2, and that gives:
x = 24.
Step 3: Finding the value of 'y'
Now that we have found the value of 'x', we can substitute it into the first equation (x + y = 37) to find 'y':
(24) + y = 37.
Solving for 'y', we get:
y = 37 - 24, and that gives:
y = 13.
Step 4: Determine the smaller number
Comparing 'x' and 'y', we can clearly see that 'y' with a value of 13 is smaller than 'x' with a value of 24. Therefore, the smaller number is 13.